The formalization of lists in the meta-language of normal forms of knowledge - Kurgaev, A. F. (Reports of the National Academy of Sciences of Ukraine, 2017)
The formalization of list-based predicates in the meta-language of normal forms of knowledge is presented for the first time, based on the known descriptions of these concepts in Prolog, which use a list-domain. Among the predica tes described are the following: adding an element to the list, removing an element, removing duplicates, checking if an element is in a list, finding the last element of a list, finding adjacent elements in a list, concatenation of lists, re versing a list, etc.